Investigating flavonoids derived from Tribulus terrestris L. as prospective candidates for Alzheimer's disease treatment: Molecular docking modeling of their interactions with physiological system receptors - Salwa Bouabdallah; Rahma Azzouz; Khattab Al-Khafaji; Mossadok Ben-Attia (Journal of Bioresources and Environmental Sciences, 2024)
Alzheimer's disease (AD) stands as the primary cause of dementia, marked by its neurodegenerative essence, which results in cognitive impairment associated with memory and a decline in functionality. Currently there is no drug which can permanently cure the nervous lesions as well as completely eradicate this pathogenesis. The aim of this research is to examine the acetylcholinesterase activity of flavonoids identified in Tribulus terrestris L. (Tt) by predicting ligand-receptor binding. The research process begins with the preparation of protein and ligand structures. Subsequently, docking is performed, interaction between protein-ligands is then analyzed and visualized. Four phytoconstituents of Tt were chosen, and molecular docking simulations revealed that all four compounds exhibited good binding affinities. Based on the predicted ADMET values using the Lipinski rule, compounds with potentially good activity were identified. The results suggest that these compounds may exhibit anti-acetylcholinesterase activity.